2022
DOI: 10.3390/bios12030141
|View full text |Cite
|
Sign up to set email alerts
|

Compact Surface Plasmon Resonance IgG Sensor Based on H-Shaped Optical Fiber

Abstract: A compact surface plasmon resonance sensor based on an H-shaped optical fiber is proposed and demonstrated. The H-shaped optical fiber was fabricated experimentally by using hydrofluoric acid to controllably corrode the polarization-maintaining fiber. A satisfactory distance between the outer surface of the fiber and the core can be achieved, and then the surface plasmon resonance effect can be excited by coating a metal film of appropriate thickness on the surface of the fiber. This technology can realize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Considering the current noise of 20 nA during the measurement, the limit of detection (LOD) of rabbit IgG can be estimated to be 150 ng/mL, which is comparable to or better than most optical sensors in the literature. For example, H-shaped SPR fiber sensor showed an LOD of 3400 ng/mL for human IgG 41 . Decoration of MoSe2 nanostructures on Au-coated optical fiber obtained an LOD of 330 ng/mL for goat-anti-rabbit IgG 42 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the current noise of 20 nA during the measurement, the limit of detection (LOD) of rabbit IgG can be estimated to be 150 ng/mL, which is comparable to or better than most optical sensors in the literature. For example, H-shaped SPR fiber sensor showed an LOD of 3400 ng/mL for human IgG 41 . Decoration of MoSe2 nanostructures on Au-coated optical fiber obtained an LOD of 330 ng/mL for goat-anti-rabbit IgG 42 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, H-shaped SPR fiber sensor showed an LOD of 3400 ng∕mL for human IgG. 41 Decoration of MoSe 2 nanostructures on Au-coated optical fiber obtained an LOD of 330 ng∕mL for goat-anti-rabbit IgG. 42 Immobilizing half-antibody fragments on an SPR fiber instead of antibody decoration reduced an LOD down to 100 ng∕mL.…”
Section: On-chip Optical Sensing With In Situ Photoelectric Conversionmentioning
confidence: 99%
“…The resonant wavelength redshifted (shifted toward longer wavelengths) from 805 nm to 1325 nm nonlinearly, meaning that the sensitivity was accelerated and enhanced with the increase in the surrounding RI. The sensitivity reached 28,100 nm/RIU at around 1.330 of the surrounding RI, which is one order of magnitude higher than conventional silica fiber SPR sensors [35]. After bio-modification, the polymer fiber SPR sensor was immersed in a PBS solution for 20 min to verify its stability.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al also reported an H‐shaped optical fiber‐based SPR sensor for the specific detection of H‐IgG on Goat aH‐IgG with a detection limits of 3.4 μg/mL. Zheng et al demonstrated the detection of H‐IgG on Goat aH‐IgG by means of a fiber optic SPR sensor (multimode fiber–noncore fiber‐multimode fiber (MMF‐NCF‐MMF) achieving a limit of detection of 1.75 μg/mL [87–89].…”
Section: Resultsmentioning
confidence: 99%